Silylboronate-Mediated Defluorosilylation of Aryl Fluorides with or without Ni-Catalyst - Zhou, Jun; Zhao, Zhengyu; Shibata, Norio (Frontiers in Chemistry, 2021)
The defluorosilylation of aryl fluorides to access aryl silanes was achieved under transition-metal-free conditions via an inert C–F bond activation. The defluorosilylation, mediated by silylboronates and KOtBu, proceeded smoothly at room temperature to afford various aryl silanes in good yields. Although a comparative experiment indicated that Ni catalyst facilitated this transformation more efficiently, the transition-metal-free protocol is advantageous from a green chemistry perspective.